Characteristics and outcome of road traffic injured patients in the emergency department of a tertiary teaching hospital in Nigeria - Afuwape, Oludolapo O.; Alonge, Temitope O.; Irabor, Achiaka E.; Balogun, Mosi J. (International Journal of Research in Orthopaedics, 2021)
Background: The exit modes from the emergency department (ED) for road traffic injury patients are namely planned discharge; admission to the wards/intensive care unit or transfer to the operating theatre; discharge against medical advice (DAMA). The aim of this study was to assess the characteristics and outcomes of non-poly-traumatized road traffic injury (RTI) related ED admissions of a tertiary health care facility in a developing country and the exit pattern from the ED. Methods: This was a retrospective hospital data-based study of outcome of RTI patients seen in the ED of a tertiary teaching hospital in Nigeria from January to December 2017. Results: 1120 RTI patients were recruited consisting of 774 males and 346 females with a male: female ratio of 2.24:1. The age range was 1 to 94 years with a mean age of 37.5±17.5 years. Peak ages were in the fourth (24.2%) and third (20.4%) decades of life respectively. 85.5% of the patients were commercial vehicles passengers. Motorcycle accidents constituted 44% of the patients while 41.8% were in cars. The commonest injuries were head injuries (31% m:f 2.7) and fractures (21% m:f 3). There were 11.5% DAMA and 7.1% deaths. Motorcycles injuries had the highest mortality rate while the motorized tricycles injuries had the highest DAMA rates. Conclusions: Motorized tricycles may be considered as a safer means of commercial mode of transportation compared to motorcycles despite its own limitations. There is a need to educate patients against the common practice of discharge against medical advice.